Association between intelligence quotient and obesity in England. Issue 2 (20th October 2020) - Jacob, Louis; Haro, Josep Maria; Smith, Lee; Koyanagi, Ai
Abstract: Introduction: In the past years, there has been a controversy regarding the potential association between intelligence quotient (IQ) and obesity. Therefore, the present study aimed to analyze the relationship between IQ and obesity in England using nationally representative community‐based data. Methods: This study used data from people who participated in the 2007 Adult Psychiatric Morbidity Survey. Verbal IQ was estimated using the National Adult Reading Test. Obesity was based on self‐reported weight and height and defined as a body mass index higher or equal to 30 kg/m 2 . Multivariable logistic regression analyses were conducted to assess the association between IQ and obesity, while adjusting for sex, age, ethnicity, marital status, qualification, employment, income, chronic physical conditions, loneliness, social support, stressful life events, smoking status, alcohol dependence, drug use, and common mental disorders. Results: There were 6798 individuals aged ≥16 years included in the present study. After adjustment for potential confounders, compared to IQ scores of 120‐129, IQ scores of 110‐119 (odds ratio [OR] = 1.16), 100‐109 (OR = 1.35), 90‐99 (OR = 1.26), 80‐89 (OR = 1.68), and 70‐79 (OR = 1.72) were associated with increased odds for obesity. Furthermore, a 10‐point decrease in IQ was associated with a 1.10‐fold increase in the odds for obesity. Conclusions: There was a negative association between IQ and obesity in the UK population. Further research is needed to provide a better understanding of the mechanisms involved in this relationship.